Geospatial Modeling of Carbon Emission Reduction Achievement in Siak Regency, Riau Province - Putri, Amaliyah; Purwanto, Ris Hadi; Soraya, Emma (Universitas Gadjah Mada, 2025)
The Siak Regency implemented the Green Siak Policy in 2016 to commit to reducing carbon emissions. This research aimed to assess land use and land cover (LULC) changes from 2016 to 2023 and make projections for 2030, quantify carbon stocks by LULC type, and estimate CO₂ emissions associated with the implementation of the Green Siak Policy. This research classified LULC using Landsat imagery. It employed the CA-Markov to project land cover in 2030 using eight driving factors: elevation, temperature, rainfall, population density, distance from roads, burned areas, state forest areas, and evidence likelihood. This research assessed carbon stocks using the Integrated Valuation of Ecosystem Services and Tradeoffs (InVEST) model and calculated CO₂ emissions based on changes in LULC and peat decomposition. The findings revealed a slight reduction in total carbon stock from 1,232.52 MtC in 2016 to 1,232.12 MtC in 2023, with annual CO₂ emissions of 1.4 MtCO₂e. Projections indicated an increase in carbon stock, expected to reach 1,232.27 MtC by 2030, with anticipated annual emissions of 1.398 MtCO₂e from 2023 to 2030. While the Green Siak Policy targeted a decrease in emissions of 23.28 MtCO₂e/year by 2030, the results indicated that the Regency achieved merely 0.03% of its target.